Introduction: Migration and Differential Labour Market Participation. Issue 4 (12th September 2017) - Netto, Gina; Craig, Gary
Abstract : Recent major political developments, including Brexit and the US presidential elections, have been strongly associated with public concerns around levels of immigration. Much of this has centred on the role of migrants in the low-skilled sectors of the economy and concerns that they have displaced members of local communities from jobs and depressed wage levels. This is despite compelling evidence that immigrants rarely take jobs from native workers in OECD countries (Constant, 2014 ) and that in the long run, the wage and employment effects of immigration in the 1990s and in the 2000s were small and always positive for less educated workers of all OECD countries (Docquier et al ., 2014 ). Recent UK specific studies have found that the impact on wages is considered to be relatively small (Dustmann et al ., 2013 ; Nickell and Salaheen, 2015 ). Notwithstanding this evidence, hostility to migrants and migration more generally has become increasingly overt, as reflected in a substantial rise in 'race' hate crimes before and following the referendum on the UK's membership of the EU in 2016 (Burnett, 2017 ).